Traces of Defeat: Why the Propaganda Effect Will Be Felt for a Long Time Yet. Issue 4 (3rd July 2016) - Gudkov, Lev
Abstract : The state monopoly over television, turning it into a vehicle of total propaganda, has over the course of time changed the structure of public and information space in Russia. Although television undoubtedly continues to occupy the dominant place in the structure of information sources, trust in the quality of broadcasts has declined sharply in recent years. As a result of the regime's efforts, the public sphere has been thoroughly sterilized. Opportunities for the representation of group interests and exchange of information have grown increasingly limited. The Russian public is once again subject to an institutional fear that goes back to Soviet times, a condition that is likely to have severe and prolonged consequences.